Dexamethasone-doped nanoparticles improve mineralization, crystallinity and collagen structure of human dentin. (March 2023) - Toledano, Manuel; Osorio, Estrella; Osorio, María T.; Aguilera, Fátima S.; Toledano, Raquel; Romero, Enrique Fernández-; Osorio, Raquel
Highlights: The use of Dex-doped NPs on demineralized dentin induces remineralization. Undoped NPs provided the lowest mechanical properties at the resin-infiltrated dentin. Zn-Dex-NPs improved mineralization, crystallinity and nature/structure of collagen. Abstract: Objectives: Bioactive materials have been used for functionalization of adhesives to promote dentin remineralization. This study aims to evaluate bonding ability and both mechanical and chemical behavior of demineralized dentin infiltrated with polymeric nanoparticles doped with dexamethasone (Dex-NPs). Methods: Dentin conditioned surfaces were infiltrated with NPs, Dex-NPs or Dex-Zn-NPs. Bonded interfaces were also created and stored for 24 h or 21d, and then submitted to microtensile bond strength testing. Dentin remineralization was analyzed by Nanohardness, Young's modulus and Raman analysis. Results: At 21d of storage, dentin treated with undoped-NPs attained the lowest nanohardness and Young's modulus . Dex-NPs and Zn-Dex-NPs increased dentin nanohardness and Young's modulus after 21d Raman analysis showed high remineralization, crystallinity, crosslinking and better structure of collagen when functionalized Dex-NPs were present at the dentin interface. Conclusions: Infiltration of dentin with Dex-NPs promoted functional remineralization as proved by nanomechanical and morpho-chemical evaluation tests. Dexamethasone in dentin facilitated crystallographic maturity, crystallinity and improved maturity and secondary structure of dentin collagen. Clinical significance: Using dexamethasone-functionalized NPs before resin infiltration is a clear option to obtain dentin remineralization, as these NPs produce the reinforcement of the dentin structure, which will lead to the improvement of the longevity of resin restorations. Graphical abstract: Image, graphical abstract